PHYTOCHEMICAL DIVERSITY AND NUTRITIONAL VALUE OF KENGER AT DIFFERENT LOCATIONS IN SULAIMANI REGION - IRAQ - Rozhgar. M. Ahmed, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Kenger (Gundelia tournefortii L.) plants were collected based on the availability of these plants in the local market to determine the nutrition value, some phytochemical content, and element content during March 2023 at the vegetative stage at thirteen different locations in the Sulaimani region. Some vegetative traits and chemical contents were studied. The results indicated that the highest content of carbohydrates was (12.670%) at Mawat, the protein was (32.703%) at Hazarmerd, and fiber was (35.620%) at Penjwen locations respectively. The analysis of Kenger edible parts (stem and leaves) through GC-MS revealed the presence of a complex mixture of compounds varying from 13 to 19 compounds among the locations. Compounds such as carboxylic acids ranged from 25.217% at Penjwen to 77.043% at Temar, terpenes ranged from 15.912% in Temar to 57.749% in Penjwen, and sterols ranged from 5.351% at Qara Dagh to 24.688% at Hazarmerd. In other locations, these compounds were detected in between those ranges, with differences in their concentrations. According to the results obtained from ICP-OES analysis, macro-elements (Ca, K, P, S, Mg, and Na) contents between the studied locations, the highest concentration of 3.127% occurred at Temar location, the lowest value was obtained at Gulp location with 2.468%, with an average of 2.811% for all locations.